Long-term stimulant treatment affects brain dopamine transporter level in patients with attention deficit hyperactive disorder. - Gene-Jack Wang (PLoS ONE, 2013)
Brain dopamine dysfunction in attention deficit/hyperactivity disorder (ADHD) could explain why stimulant medications, which increase dopamine signaling, are therapeutically beneficial. However while the acute increases in dopamine induced by stimulant medications have been associated with symptom improvement in ADHD the chronic effects have not been investigated.We used positron emission tomography and [(11)C]cocaine (dopamine transporter radioligand) to measure dopamine transporter availability in the brains of 18 never-medicated adult ADHD subjects prior to and after 12 months of treatment with methylphenidate and in 11 controls who were also scanned twice at 12 months interval but without stimulant medication. Dopamine transporter availability was quantified as non-displaceable binding potential using a kinetic model for reversible ligands.Twelve months of methylphenidate treatment increased striatal dopamine transporter availability in ADHD (caudate, putamen and ventral striatum: +24%, p<0.01); whereas there were no changes in control subjects retested at 12-month interval. Comparisons between controls and ADHD participants revealed no significant difference in dopamine transporter availability prior to treatment but showed higher dopamine transporter availability in ADHD participants than control after long-term treatment (caudate: p<0.007; putamen: p<0.005).Upregulation of dopamine transporter availability during long-term treatment with methylphenidate may decrease treatment efficacy and exacerbate symptoms while not under the effects of the medication. Our findings also suggest that the discrepancies in the literature regarding dopamine transporter availability in ADHD participants (some studies reporting increases, other no changes and other decreases) may reflect, in part, differences in treatment histories.